A comparative Study of Two Techniques for Repairing of Tracheal Defect in Dogs.: O.H. Al-hyani and A. M. Al-Hasan - Al-hyani, O. H. (The Iraqi Journal of Veterinary Medicine, 2019)
The objective of this study was designed to evaluate the possibility of repairing tracheal cartilage defect in dogs. 18 local breed dogs of both sexes was used in this study, they are allocated into 2 equal groups. A tracheal defect was induced in the cervical part of the trachea as a window about 3cm x 2cm in diameter. The defect was closed in 1st group by using polypropylene mesh and bone cement substance, while in 2nd group polypropylene mesh with fresh auto- bone marrow. Post-operative study including, clinical observation, gross pathology and histopathological evaluation was performed in all animals. The most important postoperative clinical observation was represented by subcutaneous emphysema at the site of operation in the 2nd group animals, which gradually disappeared within few days. Otherwise no other important complications was reported in both groups during the period of the experiment. The gross pathological changes and biopsy collection for all animals was done at 15, 30, 60 postoperative days. The gross examination revealed complete closing of the induced tracheal defect in all operated animals and a mild adhesion with the surrounding tissues. In both groups, the histopathological features was represented by newly granulation tissue formation and areas of hyaline cartilage degeneration and necrosis. The cartilage regeneration was showed only in 2nd group through by formation of new cartilage cells. In conclusion, it can use both techniques for reconstruction of tracheal defect in dogs but the auto bone marrow group was regarded the best due to improvement of the healing process. .